Peran dan Level Kepemimpinan Kepala Satuan Pendidikan dalam Meningkatkan Kepuasan Kerja Tenaga Kependidikan pada SMA Negeri 1 Anjongan Tahun Pelajaran 2024/2025 - mahudi, mahudi; Wicaksono, Luhur; Waruwu, Marinu (Peneliti.net, 2025)
This study is dedicated to describing the role and level of the head of the education unit in detecting obstacles and alternative solutions in order to improve the job satisfaction of education staff at SMAN 1 Anjongan in the 2024/2025 academic year. The methodology of this research is descriptive qualitative with data collection techniques through observation, interviews, and documentation carried out at SMAN 1 Anjongan. Based on the results of the study, the following conclusions are drawn. First, the efforts realized by the head of SMAN 1 Anjongan reviewed from the job description itself, honorarium/incentives/allowances, work partners, promotion opportunities, and work culture for improving job satisfaction are categorized as sufficient. Second, the obstacles include the very small number of PNS/ASN education staff and the education qualifications of education staff are not yet appropriate, thus affecting professionalism and the level of job satisfaction. Third, alternatives to overcome obstacles as an effort to improve job satisfaction reviewed from the fulfillment of the small number of education staff and their academic qualifications are by recruiting qualified alumni in the field of educational administration. In addition, carrying out IHT activities or training to improve the competence of education staff both inside and outside the school.